Pengaruh Kualitas Pelayanan,Brand Image dan Persepsi Harga Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening Di Situ Koffie Padang - Hidayatul Putri; Mellyna Eka Yan Fitri (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study examines the influence of Service Quality, Brand Image, and Price Perception on Customer Loyalty, with Customer Satisfaction as an intervening variable, at Situ Koffie Padang. Using a quantitative approach, data were collected through questionnaires distributed to 140 respondents who had prior purchasing and visiting experiences at Situ Koffie Padang. The analysis was conducted using Partial Least Squares (PLS) to assess both direct and indirect relationships among the variables.The results show that Service Quality has an indirect and insignificant effect on Customer Satisfaction; Brand Image has a positive and significant effect on Customer Satisfaction; Price Perception has a direct effect on Customer Satisfaction; Customer Satisfaction has a positive and significant effect on Customer Loyalty. Furthermore, Customer Satisfaction mediates the relationship between Brand Image and Customer Loyalty, does not mediate the relationship between Service Quality and Customer Loyalty, and mediates the relationship between Price Perception and Customer Loyalty.